Analysis of hospitalization for malignant neoplasm of the bladder in Brazil between the period 2011 to august 2022 (Research, Society and Development, 2023)
The malignant neoplasm of the bladder is a cancer that settles in the cells that cover the internal walls of the bladder, an organ of extreme importance in the storage of urine. About 90% of patients affected by the pathology only receive the diagnosis after 55 years of age, the age group in which this tumor is more present. To analyze the number and variables of hospitalization rates for malignant bladder cancer in Brazil. This is a quantitative and retrospective study with data collection from the Department of Informatics of the Unified Health System - DATASUS. The research was carried out using information from vital statistics in the Hospital Morbidity Group of the SUS (SIH/SUS). Data available from the CID 10 for both sexes, age groups and region with the highest incidence were analyzed. During the analyzed period, 181,687 cases of hospitalization for malignant neoplasm of the bladder were found. Regarding gender, 70.71% of the cases are male and 29.29% are female. Of the age groups, hospitalizations are more prevalent between 60 and 69 years of age, with 31.71% of the total cases of hospitalization for malignant neoplasm of the bladder, with 56.76% of the Southeast region having the highest cases of notifications. Bladder tumors occur two to three times more often in men than in women, which is consistent with the high rate of hospitalizations of the male population in Brazil due to bladder cancer. It is known that the peak incidence of the disease, as it is caused by failures in the genetic material, is linked to older ages, especially after 55 years of age. This factor elucidates the prevalence of hospitalizations among the elderly. The southeastern region of Brazil, being the area with the largest absolute population, and, therefore, having a greater number of elderly people, naturally presents more than half of the cases of hospitalization in the country. It appears, therefore, that the number of hospitalizations for malignant neoplasm of the bladder is higher in males, especially in the age group between 50 and 59 years, with a marked emphasis on the southeastern region of the country.